Morphology of the human aorta and age-related changes: Anatomical facts - Pornhatai Komutrattananont (2019)
© 2019 Anatomy & Cell Biology. Aorta is the largest artery in the human body. Its starting point is the aortic orifice of the aortic valve and it terminates at the level of the fourth lumbar vertebra. The main function of the aorta is to transport oxygenated blood to supply all the organs and cells. With advancing age, the structure and hence the function show progressive changes. Various changes in the aortic morphology include the luminal diameter of aorta, whole length of the aorta, thickness, the microstructural components also change, and these include collagen, elastin and smooth muscle cells. In addition, the dimensions of all segments of the aorta increase with age in both sexes. Since age is a major risk factor for degenerative change and diseases affecting the aorta, understanding the detailed anatomy of the aorta may provide essential information concerning the age-associated process of the aorta. Knowledge of the morphological changes in the aorta is also important for future clinical therapies pertaining to aortic disease. Additionally, the information regarding the structural changes with age may be applied for age determination. This review describes the overview of the anatomy of the aorta, age related changes in the morphology of the aorta and aortic diseases.